Altered anxiety-related and abnormal social behaviors in rats exposed to early life seizures - Castelhano, Adelisandra S.; Cassane, Gustavo S.; Scorza, Fulvio A.; Cysneiros, Roberta M. (Frontiers in Behavioral Neuroscience, 2013)
Neonatal seizures are the most common manifestation of neurological dysfunction in the neonate. The prognosis of neonatal seizures is highly variable, and the controversy remains whether the severity, duration or frequency of seizures may contribute to brain damage independently of its etiology. Animal data indicates that seizures during development are associated with a high probability of long-term adverse effects such as learning and memory impairment, behavioral changes and even epilepsy, which is strongly age dependent, as well as the severity, duration and frequency of seizures. In preliminary studies, we demonstrated that adolescent male rats exposed to one-single neonatal status epilepticus (SE) episode showed social behavior impairment, and we proposed the model as relevant for studies of developmental disorders. Based on these facts, the goal of this study was to verify the existence of a persistent deficit and if the anxiety-related behavior could be associated with that impairment. To do so, male Wistar rats at 9 days postnatal were submitted to a single episode of status epilepticus (SE) by pilocarpine injection (380 mg/kg, i.p.) and control animals received saline (0.9 %, 0,1mL/10 g). It was possible to demonstrate that in adulthood, animals exposed to neonatal SE displayed low preference for social novelty, anxiety-related behavior and increased stereotyped behavior in anxiogenic environment with no locomotor activity changes. On the balance, these data suggests that neonatal status epilepticus in rodents leads to altered anxiety-related and abnormal social behaviors.